Enhancing biogas production from the anaerobic treatment of municipal wastewater by forward osmosis pretreatment. (15th September 2021) - Zahedi, Soraya; Ferrari, Federico; Blandin, Gaetan; Balcazar, Jose Luis; Pijuan, Maite
Abstract: The anaerobic treatment of municipal wastewater (WW) results in low biogas production due to its relatively low concentration of organic matter. To overcome this problem, this paper assesses the potential of combining forward osmosis (FO), as a pre-treatment to concentrate real municipal WW with anaerobic digestion (AD), with the aim of enhancing methane production. A FO unit with a Toray TFC membrane sheet was operated to obtain a water recovery of 50% and 70% from municipal WW. The concentrates obtained from this process were used as substrate for biochemical methane potential (BMP) tests, where their maximum methane production potential was assessed under two different temperatures (25 °C and 35 °C). Results showed a substantial increase in the conversion of chemical oxygen demand (COD) into methane when concentrated WW was used as compared to non-concentrated WW under both temperatures, obtaining the maximum methane production at 35 °C. The occurrence of eighty pharmaceutical compounds (PhACs) during the FO process and the subsequent anaerobic treatment was also monitored. Finally, antibiotic resistance genes (ARGs) related with the main groups of antibiotics present in the WW ( bla KPC, ermB, qnrS, sul1 and tetW ) were also analyzed before and after the anaerobic treatment. A significant reduction was observed, with less ARGs being detected after the anaerobic treatment indicating that AD is a good strategy to partially remove ARGs from municipal WW. Graphical abstract: Image 1 Highlights: Forward osmosis is a suitable process to concentrate municipal wastewater. Anaerobic treatment of concentrated municipal wastewater gives higher CH4 yield. Some pharmaceutical compounds are completely removed during anaerobic treatment. Anaerobic treatment of municipal wastewater reduces antibiotic resistance genes.